2012
DOI: 10.1111/j.1466-8238.2012.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic isolation and climate govern the functional diversity of native fish communities in European drainage basins

Abstract: Aim  In times of biodiversity crisis, it is extremely important to understand diversity gradients. In particular, the study of the diversity of ecological functions is a key issue for the management of ecosystem integrity. Here we identify areas of low functional diversity of the native fish fauna in European drainage basins and we determine the relative importance of three underlying mechanisms: environmental filtering, geographic isolation and climatic history. Location  The European continent. Methods  Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 50 publications
9
87
1
Order By: Relevance
“…The existence of dissimilarity in fish species composition of different, however geographically close, drainage systems within the Tapajos National Forest indicates that geographic isolation coupled with environmental characteristics is responsible for the structuring of fish communities, in accordance with observed by Schleuter et al (2012) in temperate regions and Barros et al 2013, in tropical streams. Furthermore the smaller drainage basins can significantly influence the stream fish assemblages composition (Mendonça et al 2005; Barros et al 2013) since headwaters streams often support exclusive species that do not occur in the river system, allowing constitute single assemblages that are fundamental to compose the regional fish diversity (Paller 1994; Meyer et al 2007) and must be priority included in units conservation planning for freshwater systems.…”
Section: Discussionsupporting
confidence: 75%
“…The existence of dissimilarity in fish species composition of different, however geographically close, drainage systems within the Tapajos National Forest indicates that geographic isolation coupled with environmental characteristics is responsible for the structuring of fish communities, in accordance with observed by Schleuter et al (2012) in temperate regions and Barros et al 2013, in tropical streams. Furthermore the smaller drainage basins can significantly influence the stream fish assemblages composition (Mendonça et al 2005; Barros et al 2013) since headwaters streams often support exclusive species that do not occur in the river system, allowing constitute single assemblages that are fundamental to compose the regional fish diversity (Paller 1994; Meyer et al 2007) and must be priority included in units conservation planning for freshwater systems.…”
Section: Discussionsupporting
confidence: 75%
“…A1), maybe reflecting that biogeographical differences and ecological processes (e.g. higher interspecific competition) at local or evolutionary scales lead to increased niche specialisation towards low latitudes, as has been found in several previous studies (Griffiths 2006, Reyjol et al 2007, Mason et al 2008, Tedesco et al 2012, Schleuter et al 2012, Cirtwill et al 2015.…”
Section: Discussionsupporting
confidence: 63%
“…These authors suggest that this trend corresponds to different forms of ecosystem functioning, ranging from warm water and lower altitudinal systems (in our study represented by Araguaia basin streams) to colder and high altitudinal systems (Tocantins basin streams). Schleuter et al (2012) also observed differences between fish assemblages' functional structure of neighboring basins separated by mountain chains, as is the case of the Araguaia and Tocantins. Rahel & Hubert (1991) pointed out that transition in biological communities due to thermal conditions is expected in mountainous regions, where water temperature decreases as altitude increases.…”
Section: Discussionmentioning
confidence: 74%